If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3b + 4x = -6 Solving -3b + 4x = -6 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4x' to each side of the equation. -3b + 4x + -4x = -6 + -4x Combine like terms: 4x + -4x = 0 -3b + 0 = -6 + -4x -3b = -6 + -4x Divide each side by '-3'. b = 2 + 1.333333333x Simplifying b = 2 + 1.333333333x
| 2t+7=7 | | -21=7-4 | | 5x-4+x=-10 | | 2y+1=y+11 | | x^2-4x-4-8+x=x(x-6) | | 3xsquared+6x+4=0 | | -3+4x=-6 | | f(x)=-3x^2+5x-4 | | 3.07-x=10 | | -2b+3(3b-6)=-33+4b | | 9p-14+3(p-8)=7 | | 3y+17=y-3 | | -12=6w+18 | | 6x-10=28 | | 5x+3y=176 | | k+40=8(k+5) | | M-42=19 | | 4a-6=2a-4 | | 4x+2+x=-10 | | N-5*.66=.75 | | 2x+7-10=3 | | 2(x+1)+34=-4 | | 3x+(-6)=6 | | 3x+1=35 | | -5x+7(-4x+17)=-178 | | 3(a+1)=4(a-1.5) | | 50t=0.25t+1000 | | -2x+121=0 | | h=-16t^2+48t+7 | | 8+x=3Xx | | 5p+2p-3p= | | -8+5x=3+7(x-1) |